Randomized controlled trial of the Resilience and Coping Intervention (RCI) with undergraduate university students. Issue 1 (2nd January 2017) - Houston, J. Brian; First, Jennifer; Spialek, Matthew L.; Sorenson, Mary E.; Mills-Sandoval, Toby; Lockett, McKenzie; First, Nathan L.; Nitiéma, Pascal; Allen, Sandra F.; Pfefferbaum, Betty
ABSTRACT: Objective : The purpose of this pilot study was to evaluate the Resilience and Coping Intervention (RCI) with college students.Participants : College students (aged 18–23) from a large Midwest US university who volunteered for a randomized controlled trial during the 2015 spring semester.Methods : College students were randomly assigned to an intervention ( n = 64) or a control ( n = 65) group. Intervention participants received three 45-minute RCI sessions over subsequent weeks. All participants completed pre- and post-intervention assessments at the beginning of Week 1 and end of Week 3. Student resilience, coping, hope, stress, depression, and anxiety were assessed.Results . RCI participants reported significantly more hope and less stress and depression from Week 1 to Week 3 compared with control participants. Results for resilience also approached statistical significance. Effect sizes were small to moderate.Conclusions : This study found preliminary evidence that RCI is an effective resilience intervention for use with college students.